Disability, residential environment and social participation: factors influencing daily mobility of persons living in residential care facilities in two regions of France - Noémie Rapegno; Jean-François Ravaud (BMC, 2017)
Abstract Background Despite the context of individualization of public policies and promotion of independent living, residential care facilities (RCFs) (called "établissements medico-sociaux" in France) still represent the main system used by disabled people. Through a study of their daily mobility, this article proposes a geographical approach to the examination of factors influencing the social participation of disabled persons with motor impairments who live in residential care facilities. Methods The data were collected in three stages from several sources. We first carried out 24 semi-directive interviews among supervisory staff in all the institutions in two regions of France (Greater Paris and Upper Normandy) to better understand the nature of services offered by medico-social facilities. We next did field work in greater detail in 10 of these institutions. We selected residents by random sampling. These first stages then allowed us to study the mobility of residents and record their perceptions. We conducted participant observation and interviews with 81 disabled residents within the 10 RCF. Data analysis enabled consideration not only of the role of the residential environment in people's daily mobility, but the role of the institutions as well. Results We identified three typical profiles of mobility practices depending on the facilities: "the islanders", living in isolated facilities far from public transportation, or in so-called "difficult" neighborhoods; people who alternate individual and group mobility in a more or less large area; and "the navigators" who have high mobility over a very large area, often living in facilities located in urban areas. The study also enabled an analysis of the obstacles and facilitators inside and outside the residential facilities. These place restrictions on social participation by disabled adults. However, possibilities for individual negotiation may enable bypassing some obstacles. Conclusions The three ideal-type profiles of mobility analyzed constitute adaptations to the environment by residents and the institution. The research techniques used and the presentation of data (in the form of diagrams) enabled a better understanding of the mobility of severely disabled adults living in an institution, a population that is rarely studied.